Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
P = x4.y4 + x4 + y4 + 1
Ta có: x2 + y2 = (x + y)2 - 2xy = 10 - 2xy => x4 + y4 = (x2 + y2)2 - 2x2y2 = (10 - 2xy)2 - 2(xy)2 = 100 - 40xy + 2(xy)2
=> P = (xy)4 + 2(xy)2 - 40xy + 101 = [(xy)4 - 8(xy)2 + 16] + 10.[(xy)2 - 4xy + 4] + 45 = [(xy)2 - 4]2 + 10.(xy - 2)2 + 45
=> P > 45
Dấu "=" xảy ra <=> xy = 2
Mà có x + y = \(\sqrt{10}\) => x = \(\sqrt{10}\) - y => xy = \(\sqrt{10}\)y - y2 = 2 => y2 - \(\sqrt{10}\).y + 2 = 0
\(\Delta\) = 10 - 8 = 2 => \(y=\frac{\sqrt{10}+\sqrt{2}}{2}\)=> x = \(\frac{4}{\sqrt{10}+\sqrt{2}}=\frac{\sqrt{10}-\sqrt{2}}{2}\)
vậy P nhỏ nhất bằng 45 khi x = \(\frac{\sqrt{10}-\sqrt{2}}{2}\); \(y=\frac{\sqrt{10}+\sqrt{2}}{2}\)
P = x4.y4 + x4 + y4 + 1
Ta có: x2 + y2 = (x + y)2 - 2xy = 10 - 2xy => x4 + y4 = (x2 + y2)2 - 2x2y2 = (10 - 2xy)2 - 2(xy)2 = 100 - 40xy + 2(xy)2
=> P = (xy)4 + 2(xy)2 - 40xy + 101 = [(xy)4 - 8(xy)2 + 16] + 10.[(xy)2 - 4xy + 4] + 45 = [(xy)2 - 4]2 + 10.(xy - 2)2 + 45
=> P > 45
Dấu "=" xảy ra <=> xy = 2
Mà có x + y = \(\sqrt{10}\) => x = \(\sqrt{10}\) - y => xy = \(\sqrt{10}\)y - y2 = 2 => y2 - \(\sqrt{10}\).y + 2 = 0
\(\Delta\) = 10 - 8 = 2 => \(y=\frac{\sqrt{10}+\sqrt{2}}{2}\)=> x = \(\frac{4}{\sqrt{10}+\sqrt{2}}=\frac{\sqrt{10}-\sqrt{2}}{2}\)
vậy P nhỏ nhất bằng 45 khi x = \(\frac{\sqrt{10}-\sqrt{2}}{2}\); \(y=\frac{\sqrt{10}+\sqrt{2}}{2}\)
a, \(A=\left(\frac{1}{1-\sqrt{x}}+\frac{1}{1+\sqrt{x}}\right):\left(\frac{1}{1-\sqrt{x}}-\frac{1}{1+\sqrt{x}}\right)+\frac{1}{1-\sqrt{x}}\)ĐK : \(x>0;x\ne1\)
\(=\left(\frac{1+\sqrt{x}+1-\sqrt{x}}{1-x}\right):\left(\frac{1+\sqrt{x}-1+\sqrt{x}}{1-x}\right)+\frac{1}{1-\sqrt{x}}\)
\(=\frac{2}{1-x}.\frac{1-x}{2\sqrt{x}}+\frac{1}{1-\sqrt{x}}=\frac{1}{\sqrt{x}}+\frac{1}{1-\sqrt{x}}=\frac{1-\sqrt{x}+\sqrt{x}}{-x+\sqrt{x}}=\frac{1}{\sqrt{x}-x}\)
b, Ta có : \(x=7+4\sqrt{3}=7+2.2\sqrt{3}=\left(\sqrt{4}+\sqrt{3}\right)^2\)
\(A=\frac{1}{\sqrt{4}+\sqrt{3}-7+4\sqrt{3}}\)
\(A=x-\sqrt{x}+\dfrac{5}{4}=\left(\sqrt{x}-\dfrac{1}{2}\right)^2+1\ge1\\ A_{min}=1\Leftrightarrow\sqrt{x}=\dfrac{1}{2}\Leftrightarrow x=\dfrac{1}{4}\)
\(P=\dfrac{x+3}{\sqrt{x}+3}\) (ĐK: \(x\ge0\))
Mà: \(x\ge0\Rightarrow\left\{{}\begin{matrix}x+3\ge3\\\sqrt{x}+3\ge3\end{matrix}\right.\) nên:
\(P=\dfrac{x+3}{\sqrt{x}+3}\ge\dfrac{3}{3}=1\)
Dấu "=" xảy ra:
\(\dfrac{x+3}{\sqrt{x}+3}=1\)
\(\Leftrightarrow x=\sqrt{x}\)
\(\Leftrightarrow x=0\left(tm\right)\)
Vậy: \(P_{min}=1\) khi \(x=0\)